2020
DOI: 10.1017/s0007485319000865
|View full text |Cite
|
Sign up to set email alerts
|

Assessment irradiation effects on different development stages of Callosobruchus maculatus and on chemical, physical and microbiological quality of cowpea seeds

Abstract: AbstractIrradiation is a physical, environmentally friendly treatment which does not leave any residues in the product. It is increasingly used as an alternative to methyl bromide and other chemical fumigants for disinfestation of insect pest in stored grains. In this research, we try to evaluate the effect of low gamma irradiation doses in the range of 50–1200 Gy on the different stages of Callosobruchus maculatus. It was found that no adults emerged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…Contrary to these results, Dongre et al (1997) observed 50% adult emergence after irradiating pupae at 150 Gy. A higher dose of 650 Gy was required to completely inhibit adult emergence after irradiation (Hammad et al, 2020). Diop et al (1996) maintained 214 eggs of C. maculatus and irradiated them at their pupal stage at 100 Gy, but, only one adult emerged out after irradiation, which is similar to our study.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Contrary to these results, Dongre et al (1997) observed 50% adult emergence after irradiating pupae at 150 Gy. A higher dose of 650 Gy was required to completely inhibit adult emergence after irradiation (Hammad et al, 2020). Diop et al (1996) maintained 214 eggs of C. maculatus and irradiated them at their pupal stage at 100 Gy, but, only one adult emerged out after irradiation, which is similar to our study.…”
Section: Resultssupporting
confidence: 90%
“…Protein content varied from 21.37% to 24.93%. Hammad et al (2020) irradiated cowpea grains with 650 Gy and found no significant difference in moisture, protein, lipid, ash and carbohydrate content of cowpea grains immediately after irradiation and also after three months of irradiation. Likewise, Al-Kaisey et al (2003) reported that there was no significant difference in the protein and carbohydrate content of broad bean (Vicia faba) irradiated at a dose ranging from 0 to 10 KGy.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, the eggs that were more than 36 h old have shown more resistance to CP treatment as the embryogenesis process already produced an embryo inside the eggs. Similar results were obtained in Hammad et al (2020) study, where one‐day old C. maculatus eggs showed less resistance to irradiation treatment than 3 days old eggs (dose: 200 Gy, hatchability of 3 days old egg: 52.3%, 1‐day‐old age: 44.8%). Thus, the mortality of eggs will not be the same for all the eggs, and it will vary based on the time interval between the treatment and oviposition.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, irradiation for phytosanitary purposes is a physical and environmentally friendly treatment, often used for the disinfestation of insect pests in grains. Accordingly to Hammad et al (2020) low doses of irradiation on eggs, larvae or pupae of Callosobruchus maculatus did not give rise to any emergent adult beetle, and the same result was observed when irradiating parental adults. The irradiation dose required for cowpea seed weevil disinfestation was 650 Gy, a dose that did not affect the physical and chemical characteristics of cowpea seeds, although it reduced their microbial load very slightly.…”
Section: Food Preservationsupporting
confidence: 65%